Real-time label-free three-dimensional invasion assay for anti-metastatic drug screening using impedance sensing - Ding, Kai; Li, Hailong; Xu, Qian; Zhao, Yongmei; Wang, Kaikai; Liu, Tianqing (Frontiers in Pharmacology, 2024)
Tumor metastasis presents a formidable challenge in cancer treatment, necessitating effective tools for anti-cancer drug development. Conventional 2D cell culture methods, while considered the "gold standard" for invasive studies, exhibit limitations in representing cancer hallmarks and phenotypes. This study proposes an innovative approach that combines the advantages of 3D tumor spheroid culture with impedance-based biosensing technologies to establish a high-throughput 3D cell invasion assay for anti-metastasis drug screening through the multicellular tumor spheroids. In addition, the xCELLigence device is employed to monitor time-dependent kinetics of cell behavior, including attachment and invasion out of the 3D matrix. Moreover, an iron chelator (deferoxamine) is employed to monitor the inhibition of epithelial-mesenchymal transition in 3D spheroids across different tumor cell types. The above results indicated that our integrated 3D cell invasion assay with impedance-based sensing could be a promising tool for enhancing the quality of the drug development pipeline, providing a robust platform for predicting anti-metastatic drug efficacy and safety before advancing to preclinical or clinical trials.